-2(v+2)=2v-4+2(3v+1)

Simple and best practice solution for -2(v+2)=2v-4+2(3v+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(v+2)=2v-4+2(3v+1) equation:


Simplifying
-2(v + 2) = 2v + -4 + 2(3v + 1)

Reorder the terms:
-2(2 + v) = 2v + -4 + 2(3v + 1)
(2 * -2 + v * -2) = 2v + -4 + 2(3v + 1)
(-4 + -2v) = 2v + -4 + 2(3v + 1)

Reorder the terms:
-4 + -2v = 2v + -4 + 2(1 + 3v)
-4 + -2v = 2v + -4 + (1 * 2 + 3v * 2)
-4 + -2v = 2v + -4 + (2 + 6v)

Reorder the terms:
-4 + -2v = -4 + 2 + 2v + 6v

Combine like terms: -4 + 2 = -2
-4 + -2v = -2 + 2v + 6v

Combine like terms: 2v + 6v = 8v
-4 + -2v = -2 + 8v

Solving
-4 + -2v = -2 + 8v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-8v' to each side of the equation.
-4 + -2v + -8v = -2 + 8v + -8v

Combine like terms: -2v + -8v = -10v
-4 + -10v = -2 + 8v + -8v

Combine like terms: 8v + -8v = 0
-4 + -10v = -2 + 0
-4 + -10v = -2

Add '4' to each side of the equation.
-4 + 4 + -10v = -2 + 4

Combine like terms: -4 + 4 = 0
0 + -10v = -2 + 4
-10v = -2 + 4

Combine like terms: -2 + 4 = 2
-10v = 2

Divide each side by '-10'.
v = -0.2

Simplifying
v = -0.2

See similar equations:

| T-19=17 | | 72x+16=64x+40 | | -119=3(3-4x)-4x | | .20x+8=13 | | 15+8v=8v-3(v-3) | | -4(-6c+7)=35 | | 2x+35+5x+5=180 | | .25x+7=9 | | 5x+5+2x+35=90 | | 4x^3-7x^2-5x-6= | | b+1-3b=(4+6b)-7 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | 6x-3=6x+11 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | -7n+10+9n=18 | | -7n+10+9n=18 | | -173=7+4(7k-3) | | 6y+3x=32 | | 150+35x=45 | | 30=-4a+10 | | ax-6=t | | -10h(h-2)-4=36 | | H=297+-4.4t | | q+r=37 | | -2a+5=19 | | 34-(-4)=x | | 46=2x+4x+4 | | -2(7w-2)+5w=2+2(3w-8) | | q-2r=4 | | 27+5n=7(4n-6) |

Equations solver categories